Investigating the role of proteins in melanosome transport - Kajana, Sivarasa (2018)
The specialized epidermal cells produce melanin within the organelles referred to as melanosomes. These melanosomes are believed to be transported along the microtubules from the perinuclear region to the actin and then the tri-partile complex of myosin Va, Melanophilin and Rab27a move the melanosomes along the actin filaments to the plasma membrane. Any defectiveness or disruption of these proteins leads to several disorders such as Hermansky-Pudlak Syndrome (HPS), Chediak-Higashi Syndrome and Griscelli Syndrome which are caused due to defects in genes that control organelle biogenesis, organelle motility or cargo transport within cells. The key aim of this project is to study the involvement of the proteins myosin Va, Rab27a and its effector proteins melanophilin and slp2-a. The experiment fluorescence Recovery after photobleaching(FRAP) was performed in different mutant cell lines such as melan-leaden (lacks melanophilin), melan-d (lacks myosin Va) and melan-ash (lacks Rab27a). We then transfected members of the tri-partile complex into these cell cells to observe their effect on melanosome transport. A mutant Rab27a which highly reduces the binding of its effectors slp2 and melanophilin was also used to investigate the binding dynamics of these effector proteins with Rab27a. Finally, these findings led to the idea of constructing a chimeric molecule where the RBD region of melanophilin been replaced with the RBD region of Slp2 and was expected to have a stable interaction with Rab27a. From these experiments, it was identified that melanophilin has a dynamic interaction with Rab27a and Slp2 has a stable interaction. It was understood that the Rab binding region(RBD) of slp2 and melanophilin perform a major part in controlling the nature of movement with Rab27a.